A little history attached to them : authenticité et crédibilité du témoignage matériel dans les collections anthropologiques, 1850-1900 - Ricardo Roque (Revue d’Histoire des Sciences Humaines)
In this paper I examine the significance of histories and documentation in association with collections as technologies of credibility in nineteenth century racial anthropology. Drawing on the analysis of catalogues and archives of anthropological collections, I argue that connecting histories and documentation was important to perform the authenticity of skulls as scientific objects and thereby guarantee the credibility of material testimony in racial anthropology. This economy of authenticity of biological materials implied an economy of credibility of the testimony of documents. The reliability of skulls as racial evidence had to be attested by trustworthy histories. The credibility of the latter also had to be guaranteed by three main forms of authentication: anatomical certification; sociological assurance; and rhetorical authentication.